Psikoedukasi Keluarga pada Klien dan Caregiver Lansia dengan Hipertensi - Dwiyantoro Dwiyantoro; Herni Susanti; Mustikasari Mustikasari; Ria Utami Panjaitan; Ice Yulia Wardani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe family psychoeducation for elderly clients and caregivers with hypertension. This research method uses a case study method to analyze in-depth the benefits of family psychoeducation for clients and elderly caregivers with hypertension. The results showed that the benefits of providing family psychoeducation impacted clients and caregivers by increasing knowledge from those who did not understand hypertension. To become more understanding about hypertension, caregivers were able to practice dealing with stress and burdens in the family. In conclusion, applying family psychoeducation nursing actions to elderly clients and caregivers with hypertension can increase knowledge about hypertension and assist caregivers in providing care to hypertensive clients in managing stress and family burdens so that caregivers can carry out their activities and roles optimally. Keywords: Caregiver, Hypertension, Elderly, Psychoeducation